Increasing Reproductive Health Knowledge in Adolescents - Dini Afriani; Serly Marcelina; Grace Yobelia Sinyo; Chalza Nurhaeda Fazriani; Novia Friskilla (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Adolescent reproductive health is a healthy condition that concerns the reproductive system, functions and processes possessed by adolescents. In Ranggasari Village there are still many teenagers who do not know more about reproductive health. The implementation of this community service aims to help adolescents in Ranggasari Village who need a broader view of reproductive health so that they are able to protect themselves from reproductive health problems and also to empower adolescents in general health aspects and reproductive health in particular so that they can grow and develop into teenagers who are responsible for social behavior and sexual behavior. This community service activity was carried out in October 2022. The focus of this community service activity is increasing public knowledge, especially adolescents, regarding reproductive health. The community conducts a pre-test before providing counseling with the aim of getting an overview of community knowledge, especially adolescents, regarding reproductive health. Counseling is carried out offline, including counseling on reproductive health. The community returned to post-test after being given counseling with the aim of knowing the description of community knowledge after being given counseling. As a result, after being given counseling, people's knowledge about reproductive health has increased. This activity ran smoothly and the community was very enthusiastic about listening to the extension.